Efecto de la aplicación de extractos vegetales en la producción de plántulas de cucurbitáceas (Cucumis sativus L. y Cucumis melo L.). - Cañizares Caiza, Carmen Carolina (2024)
The present research was carried out in the main cantonal of La Maná, to evaluate the effect of the application in plant extracts on the production of cucumber (Cucumis sativus L.) and melon (Cucumis melo L.) seedlings. A completely randomized experimental design (CRD) was used, with a factorial arrangement ABC, where factor A was the cucumber species (a1. Cucumber and a2. Melon), factor B was the plant extracts (b1. Cinnamon and b2. Coffee), and factor C corresponded to the dilution doses (c1. 1 g/L water; c2. 0.5 g/L water; and c3. 0.1 g/L water), resulting in 12 treatments plus two controls (223+2). The evaluation variables in the research were the height and diameter of seedlings, number of functional leaves, length and width of leaves, length, volume, and mass of roots, leaf mass, dry matter, pest incidence, and economic analysis of the treatments. The best results obtained in T8 were: Melon with Cinnamon at 1g/L water, with the longest roots at 11.49 cm, the largest volume at 0.47 mm, and consequently, the highest mass at 0.56 g. Additionally, this treatment showed no incidence of pests. T6: Cucumber with Coffee at 0.1 g/L water was the treatment that achieved the best results in terms of the number of functional leaves (2.9 units) and the largest leaves (7 cm long and 7.98 cm wide). It was also the second or third-best treatment in most other variables. The treatment with the highest dry matter was T7: Cucumber with Water at 44.7%. However, the most profitable treatment was T7: Cucumber with Water at 110.6%. It is important to note that this economic analysis only considers value in terms of the number of plants produced and not in terms of their quality.